Multiband photometry of Martian Recurring Slope Lineae (RSL) and dust-removed features at Horowitz crater, Mars from TGO/CaSSIS color observations. (May 2022) - Munaretto, G.; Pajola, M.; Lucchetti, A.; Cremonese, G.; Simioni, E.; Re, C.; Bertoli, S.; Tornabene, L.; McEwen, A.S.; Becerra, P.; Rangarajan, V.G.; Valantinas, A.; et al.
Abstract: Recurring Slope Lineae (RSL) are narrow, dark streaks typically lengthening down Martian steep slopes during warm seasons, fading during the cold ones and regularly recurring every Martian year. Their origin is still debated. Although initially interpreted as possible flows of seeping water, either coming from a subsurface aquifer or through atmospheric processes, recent studies favor a dry granular flow origin. To date, the nature and formation mechanism of RSL represent an open science question about present-day surface processes occurring on Mars. In this study, we analyze color observations of RSL at Horowitz crater, acquired with the Colour and Surface Science Imaging System (CaSSIS) on board ESA's ExoMars Trace Gas Orbiter (TGO) mission. We compare the relative photometry of RSL with respect to nearby terrains with the relative reflectance of dust-removed surfaces, including dust-devil tracks, in the four CaSSIS filters to help assess their properties. Comparing our relative photometry with dust-deposition and soil-wetting models coming from published laboratory experiments, we find that the former results provide a better fit to the observations than the latter, hence supporting a dry origin for Horowitz RSL. Graphical abstract: Image 1 Highlights: Recurring Slope Lineae are martian surface feature which origin is still debated. We present the first 4 band relative albedo measurements of RSL performed with CaSSIS data. Our analysis support a dry origin for RSL.